SYNTHESIS AND CHARACTERIZATION OF ECOFRIENDLY SOYPROTEIN CONCENTRATE/CLOISITE 30B NANOCOMPOSITES FOR FILM MAKING - NABA KISHORE PRADHAN,; MIRA DAS,; P.L NAYAK, (International Journal of Pharma and Bio Sciences, 2016)
Biodegradable films of Soy Protein Concentrate (SPC) and Cloisite 30B (C 30B) have been prepared by melt extrusion method in which C 30B was used as a nanofiller. The structures and properties of the films were characterised by FTIR, XRD, SEM, TEM, TGA and tensile testing. Soy Protein Concentrate/Cloisite 30B hybrids showed an intercalated nanostructure due to the compatibility of the two components. The biodegradability of the films was investigated by three different methods like soil burial, compost burial and enzymatic degradation. In all the three methods the films containing C 30B clay were found to be more biodegradable than those SPC films without C30B.